2013
DOI: 10.1002/anie.201307875
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Structural Revision of the Alkaloid Incargranine B

Abstract: Seeing double: Consideration of the biosynthetic origins of incargranine B, which was originally assigned an unprecedented indolo[1.7]naphthyridine structure, led to the proposal of a dipyrroloquinoline framework as a more biosynthetically feasible structure (see scheme; Piv=pivaloyl). This hypothesis was validated by a short biomimetic synthesis of incargranine B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 11 publications
1
32
0
Order By: Relevance
“…3). 16 We proposed phenylethanoid-diamine 11 represented a reasonable biosynthetic precursor to incargranine B (Scheme 2b). Oxidative deamination of diamine 11 could give an aldehyde 12, which, following intramolecular condensation, would give an N-aryl enamine 13.…”
Section: Incargranine Bmentioning
confidence: 99%
See 1 more Smart Citation
“…3). 16 We proposed phenylethanoid-diamine 11 represented a reasonable biosynthetic precursor to incargranine B (Scheme 2b). Oxidative deamination of diamine 11 could give an aldehyde 12, which, following intramolecular condensation, would give an N-aryl enamine 13.…”
Section: Incargranine Bmentioning
confidence: 99%
“…16 The acetal protected cyclisation precursor 15 (prepared in 3 steps) was exposed to 2 M aqueous HCl to deprotect the aldehyde and induce the condensation/Mannich/S E Ar reaction sequence, giving a mixture of two dimeric products 16 and 17, in 50% isolated yield. Analysis of the 1 H and 13 C NMR spectra for the minor product, 17, revealed key similarities with the NMR data reported for incargranine B.…”
mentioning
confidence: 99%
“…These results indicated that the biosynthetic consideration combined with the theoretical calculation of NMR data is helpful to accurately elucidate the complicated structure of natural products. [20] …”
mentioning
confidence: 99%
“…There are no reports of 1,2-dimethylenecyclopentane-type structures undergoing Diels-Alder dimerizations under ambient conditions. [13] The synthesis began with the high yielding conversion of vanillin into its benzene sulfonate ester, a process that could be easily conducted on large scale (Scheme 2). b) Schroeder's proposed biosynthesis of the ramonanins A-D (3-6).…”
mentioning
confidence: 99%
“…[12] To investigate the nature of this fascinating biosynthetic dimerization we chose to pursue a total synthesis of the ramonanin natural products (3)(4)(5)(6). [13] The synthesis began with the high yielding conversion of vanillin into its benzene sulfonate ester, a process that could be easily conducted on large scale (Scheme 2). Two molecules of the resulting aldehyde 8 were united through an acetylene unit in a one-pot sequence to afford multigram quantities of diacetate 9 as a 1:1 mixture of diastereomers.…”
mentioning
confidence: 99%